Control of Orthodontic Tooth Movement by Nitric Oxide Releasing Nanoparticles in Sprague-Dawley Rats - Crawford, Derrick; Lau, Tommy C.; Frost, Megan C.; Hatch, Nan E. (Frontiers in Materials, 2022)
Orthodontic treatment commonly requires the need to prevent movement of some teeth while maximizing movement of other teeth. This study aimed to investigate the influence of locally injected nitric oxide (NO) releasing nanoparticles on orthodontic tooth movement in rats. Materials and Methods: Experimental tooth movement was achieved with nickel-titanium alloy springs ligated between the maxillary first molar and ipsilateral incisor. 2.2 mg/kg of silica nanoparticles containing S-nitrosothiol groups were injected into the mucosa just mesial to 1st molar teeth immediately prior to orthodontic appliance activation. NO release from nanoparticles was measured in vitro by chemiluminescence. Tooth movement was measured using polyvinyl siloxane impressions. Bones were analyzed by microcomputed tomography. Local tissue was assessed by histomorphometry. Results: Nanoparticles released a burst of NO within the first hours at approximately 10 ppb/mg particles that diminished by 10 × to approximately 1 ppb/mg particles over the next 1–4 days, and then diminished again by tenfold from day 4 to day 7, at which point it was no longer measurable. Molar but not incisor tooth movement was inhibited over 50% by injection of the NO releasing nanoparticles. Inhibition of molar tooth movement occurred only during active NO release from nanoparticles, which lasted for approximately 1 week. Molar tooth movement returned to control levels of tooth movement after end of NO release. Alveolar and long bones were not impacted by injection of the NO releasing nanoparticles, and serum cyclic guanosine monophosphate (cGMP) levels were not increased in animals that received the NO releasing nanoparticles. Root resorption was decreased and periodontal blood vessel numbers were increased in animals with appliances that were injected with the NO releasing nanoparticles as compared to animals with appliances that did not receive injections with the nanoparticles. Conclusion: Nitric oxide (NO) release from S-nitrosothiol containing nanoparticles inhibits movement of teeth adjacent to the site of nanoparticle injection for 1 week. Additional studies are needed to establish biologic mechanisms, optimize efficacy and increase longevity of this orthodontic anchorage effect.